The Optimasi Rendemen Minyak Mikroalga Laut Nannochloropsis sp. Menggunakan Metode Tekanan Osmotik NaCl(aq) - Muhaemin, Moh; Pasa, Zelang; Ali, Mahrus (Universitas Bangka Belitung, 2023)
Biodiesel is derived from natural fats such as vegetable or animal oils. This study uses a type of microalgae that can produce products and has the potential as biodiesel fuel, namely Nannochloropsis sp. The purpose of this study was to determine the effect of osmotic shock on the oil yield of Nannochloropsis sp. to determine the optimum osmotic shock, and to determine the composition of fatty acid content in the microalgae Nanochloropsis sp. in both wet and dry conditions. The extraction process in this study used five variations of osmotic shock, namely 0, 30, 60, 90 and 120 atm. The results showed that osmotic shock had an effect on both oil yields of Nannochloropsis sp. both in wet conditions (R=0.890 Sig<0.043) and Nannochloropsis sp. dry conditions (R=0.916 Sig<0.029). So that the higher the osmotic shock applied, the higher the yield of Nannochloropsis sp. wet and oil yield of Nannochloropsis sp. dry. then the osmotic stress of 120atm is good for extracting the oil of Nannochloropsis sp. Each result obtained is Nannochloropsis sp. wet atm 120 atm (3.96 %) and for Nannochloropsis sp. dry 120 atm (2.60 %). Results of GC Chromatogram analysis on oil yield of Nannochloropsis sp. 13 fatty acids were found including saturated fat: octanoate (C8:0), laurate (C12:0), tetradecanoate (C14:0), heptadecanoate (C17:0), arachidate (C20:0), heneicosanoate (C21:0), tricosanoate (C23:0), lignocerate (C24:0) dan lemak tak jenuh palmitoleate (C16:1), oleic (C18:1), linolelaidic (C18:2), nervonate (C24:1), dan docosahexaenoate (C22:6).